Vahan E. Hovhannisyan - Piliposyan, Ashot S.; Areshian, Gregory E. (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
This marvelous, deeply moving, and often-cited canto by Alfred, Lord Tennyson reflects the feelings of many people who new Vahan Hovhannisyan, a person of enormous commitment, courage, and thoughtfulness. Today we remember his love for and devotion to the cultural heritage of his country and its history, and also to the present and future of Armenia and the Armenian people.